A multicenter, prospective, randomized trial of the efficacy and safety of Alflutop® in an alternating dosing regimen versus the standard one. Communication 1: Evaluation of the efficacy of the drug in different treatment regimens - L. I. Alekseeva; E. A. Taskina; A. M. Lila; V. I. Mazurov; N. A. Shostak; E. I. Shmidt; E. P. Ilivanova (Современная ревматология)
Using of more convenient drug regimens is one of the ways to increase patient adherence to treatment for osteoarthritis (OA).Objective: to evaluate the efficacy of Alflutop® in an alternating dosing regimen versus its standard administration to patients with knee OA. Patients and methods. The investigation included 130 randomized patients who had Kellgren—Lawrence Grade II—IIIprimary tibiofemoral knee OA with pain intensity on walking at least 40 mm on a visual analogue scale and needed to take nonsteroidal anti-inflammatory drugs (at least 30 days in the previous 3 months). The patients were divided into two groups: 1) those who received Alflutop® 2 ml intramuscularly (IM) every other day (a total of 10 injections); 2) those who used the drug 1.0 ml IM daily for 20 days. The duration of the investigation was 14 weeks. Results and discussion. Just on days 20/21 of treatment, the patients of both groups were recorded to have statistically significant reductions in knee pain on walking (p<0.001) and in all WOMAC indices (pain, stiffness, functional failure). There were further reductions in pain and WOMAC within one month or more after completion of therapy (p<0.001), which suggests that the drug has a pronounced after-effect. A statistically significant improvement in quality of life according to the EQ-5D was also noted throughout the study period (p<0.001). The assessment made according to the OMERACT-OARSI criteria was also consistent with the findings. By the end of treatment, its respondents were 84.6 and 81.5% of the patients in Groups 1 and 2, respectively.Conclusion. The data from this investigation confirm the comparable high efficacy of Alflutop® used in both standard and alternating treatment regimens. During treatment, there was a significant reduction in pain intensity and improvements in knee joint function and quality of life. The investigation has shown that the drug can be used at a dose of 1 ml not daily for 20 days, but also at 2 ml every other day for 10 days.